2021
DOI: 10.1080/0020739x.2021.1962555
|View full text |Cite
|
Sign up to set email alerts
|

The rapid move to online mathematics support: changes in pedagogy and social interaction

Abstract: The dramatic changes brought on by the COVID-19 pandemic have changed the way in which mathematics and statistics support is offered. Students and staff have been presented with new opportunities and challenges. One-on-one interviews were conducted late in 2020 with 23 students and staff who had experience with fully online mathematics and statistics support. The interviewees were from University College Dublin, Ireland, and Western Sydney University, Australia. Utilising thematic analysis, five themes around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
(76 reference statements)
0
3
0
6
Order By: Relevance
“…It was notable that in both universities involved in the Mullen et al study that the numbers of students availing of MLS decreased significantly during the COVID-19 closures ( [22], [23]). A similar drop in attendance was seen in the Mathematics Support Centre in Maynooth University [20].…”
Section: Provision Of Online Supportmentioning
confidence: 97%
See 1 more Smart Citation
“…It was notable that in both universities involved in the Mullen et al study that the numbers of students availing of MLS decreased significantly during the COVID-19 closures ( [22], [23]). A similar drop in attendance was seen in the Mathematics Support Centre in Maynooth University [20].…”
Section: Provision Of Online Supportmentioning
confidence: 97%
“…Some did not know about the scheme, others said that they had no time, did not need the extra help, or preferred to work alone. Mullen et al [22] reported that tutors in WSU encouraged group work in their online sessions but sometimes found it difficult to get students to engage. Some students said that it was easier to avoid contributing to discussions online than it would be in-person.…”
Section: Provision Of Online Supportmentioning
confidence: 99%
“…En plus de s'inquiéter pour leur santé et leur sécurité et celles de leurs élèves, les enseignants ont dû se mobiliser rapidement lors de la fermeture des écoles pour trouver des façons alternatives d'interagir avec les jeunes et de les scolariser (Mullen et al, 2021). En effet, les mesures mises en oeuvre par les gouvernements pour contrer la propagation de la COVID-19 ont forcé une transition « spontanée » et non prévue de l'enseignement en présentiel à l'enseignement virtuel 2 , laissant peu de temps aux enseignants pour se former adéquatement (Gopalan et al, 2021 ;Seke, 2020 ;Westwick & Morreale, 2020).…”
Section: Problématiqueunclassified
“…Le premier niveau représente l'état de besoin. Avec le passage au virtuel, certains enseignants éprouvent de la difficulté à s'approprier les technologies, à interagir avec les élèves et à les engager dans leurs apprentissages (Kim & Asbury, 2020 ;Mullen et al, 2021). Dans ce cas, le nouvel objet de l'activité peut être de trouver une méthode pour remédier à ces difficultés.…”
Section: La Résolution Des Contradictions Vécues Par Les Enseignants Durant La Pandémieunclassified
“…Berdasarkan artikel terpilih yang diterbitkan dari tahun 2018 sehingga bulan April 2022, kajian ini mendapati bahawa kajian cabaran pengajaran dan pembelajaran matematik dalam talian paling banyak diterbitkan pada tahun 2021 (Rajah 2). Daripada 20 artikel yang terpilih, terdapat 3 artikel yang diterbitkan pada tahun 2018 (Reju & Jita, 2018;Msomi & Bansilal, 2018;Moradi et al, 2018), 1 artikel diterbitkan pada tahun 2019 (Thompson & McDowell, 2019), 3 artikel diterbitkan pada tahun 2020 (Naidoo, 2020;Cassibba et al, 2020;Wang et al, 2020), 10 artikel diterbitkan pada tahun 2021 (Lishchynska et al, 2021;Fhloinn & Fitzmaurice, 2021;Sedaghatjou et al, 2021;Bringula et al, 2021;Cao et al, 2021;Calder et al, 2021;Mukuka et al,2021;Lambert & Schuck, 2021;Hite et al, 2021;Jeong & González-Gómez, 2021) dan 3 artikel diterbitkan pada tahun 2022 (Maarif et al, 2022;Radmehr & Goodchild, 2022;Mullen et al, 2022).…”
Section: Tahun Penerbitanunclassified